Untold diversity of floral rewards in Cypella (Tigridieae: Iridaceae) and related genera: distribution and anatomy. (4th December 2021) - Pastori, Tamara; Kuhn, Sofia Aumond; De Souza-Chies, Tatiana Teixeira; Silvério, Adriano; Mastroberti, Alexandra Antunes; Eggers, Lilian; Chauveau, Olivier; Mariath, Jorge Ernesto De Araujo
Abstract: Floral rewards are important elements in plant–pollinator interactions and can play an essential role in the diversification of species. The identification of these rewards has been neglected in species of Tigridieae (Iridaceae), one of the few angiosperm groups to offer lipids, considered a specialized reward. We identify and characterize the secretory structures of floral rewards in Cypella and related genera ( Calydorea, Catila, Herbertia, Onira and Kelissa ). Our results reveal that there are trichomatic elaiophores in the tepals of Cypella, Kelissa, Onira and Herbertia and staminal nectaries in the connectives of the anthers of Cypella and Onira . There is an unusual combination of floral rewards in Cypella and Onira, demonstrating a unique pattern in Iridaceae of the American continent.